De Novo Central Vein Stenosis in Hemodialysis Patients Following Initial Tunneled Central Vein Catheter Placement. Issue 1 (27th January 2022) - Al-Balas, Alian; Almehmi, Ammar; Varma, Rakesh; Al-Balas, Hassan; Allon, Michael
Key Points: The overall incidence of de novo significant central vein stenosis was 13% in hemodialysis patients after their first tunneled catheter. The likelihood of central venous stenosis (CVS) was substantially greater in patients with at least 6 months of central venous catheter (CVC) dependence. Our study did not observe a significant association of central venous stenosis with the location of initial tunneled central venous catheter. Visual Abstract: Abstract : Background: Central vein stenosis (CVS) is a common complication in hemodialysis patients following tunneled central venous catheter (CVC) insertion. Little is known about its incidence, association with patient characteristics, or relationship with duration of CVC placement. We systematically evaluated central vein stenosis in hemodialysis patients receiving their first CVC exchange at a large medical center. Methods: All new hemodialysis patients underwent an ultrasound before their internal jugular tunneled CVC placement, to exclude venous stenosis or thrombosis. After the initial CVC insertion, if the patients were referred for CVC exchange due to dysfunction, a catheterogram/venogram was performed to assess for hemodynamically significant (≥50%) central vein stenosis. During a 5-year period (January 2016 to January 2021), we quantified the incidence of CVS in patients undergoing CVC exchange. We also evaluated the association of central vein stenosis with patient demographics, comorbidities, and duration of CVC dependence before exchange. Results: During the study period, 273 patients underwent exchange of a tunneled internal jugular vein CVC preceded by a catheterogram/venogram. Hemodynamically significant CVS was observed in 36 patients (13%). CVS was not associated with patient age, sex, race, diabetes, hypertension, coronary artery disease, peripheral artery disease, or CVC laterality. However, the frequency of CVS was associated with the duration of CVC dependence (26% versus 11% for CVC duration ≥6 versus <6 months: odds ratio (95% CI), 3.17 (1.45 to 6.97), P =0.003). Conclusions: Among incident hemodialysis patients receiving their first tunneled internal jugular CVC exchange, the overall incidence of de novo hemodynamically significant central vein stenosis was 13%. The likelihood of CVS was substantially greater in patients with at least 6 months of CVC dependence.